2008
DOI: 10.2515/therapie:2008046
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Clinical Research Performances in France?

Abstract: -The general objective of this study was to proceed an inventory of measures which could help to improve the efficiency of clinical research in France. Method. Thanks to the discussion between the members of the round-table conference (composed of medical doctors (MD)/investigators; hospital managers; representatives of industrial promoters; general practitioners...), we have looked over the difficulties that meets clinical research in France nowadays. Results. We identified four fields of action: 1) availibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Galvin et al [ 14 ] showed that inadequate procedures and the framework of opinion about the process of inclusions are both predictors of inclusion: OR 4.7, 95% CI (12-18.7), OR 6.8, 95% CI (1.4-32.3). Diebolt and Pletan [ 19 ] clearly showed that the internal organization of research centers in France has major deficiencies particularly with regard to bureaucracy and lack of motivation of practicing physicians in the centers. They do not feel involved in the procedures because of a lack of staff meetings or information on research concerning upcoming clinical trials or the progress of trials already underway.…”
Section: Discussionmentioning
confidence: 99%
“…Galvin et al [ 14 ] showed that inadequate procedures and the framework of opinion about the process of inclusions are both predictors of inclusion: OR 4.7, 95% CI (12-18.7), OR 6.8, 95% CI (1.4-32.3). Diebolt and Pletan [ 19 ] clearly showed that the internal organization of research centers in France has major deficiencies particularly with regard to bureaucracy and lack of motivation of practicing physicians in the centers. They do not feel involved in the procedures because of a lack of staff meetings or information on research concerning upcoming clinical trials or the progress of trials already underway.…”
Section: Discussionmentioning
confidence: 99%